Quo-Vadis Ekonomi Syariah di Indonesia - Fauziah Nur Saidah; Lucky Nugroho; Yosi Mardoni (Baca Dulu Publisher, 2024)
This research article aims to identify strategies and innovations to overcome challenges and maximize opportunities in the Islamic economy in Indonesia. Therefore, the problem formulations in this research include: (i) What are the basic principles of Islamic economics? (ii) What are the challenges and opportunities of implementing Islamic economics in Indonesia? (iii) What are the strategies and innovations to overcome challenges and maximize opportunities of Islamic economics in Indonesia? Furthermore, the method used in this research is to use qualitative descriptive analysis to collect information from various sources, such as books, government reports, academic literature, and journals related to the problems and opportunities of implementing Islamic economics in Indonesia. The results of this study are that there are several key strategies, including increasing public literacy, increasing Islamic financial inclusion through digitalization, developing Islamic fintech, halal e-commerce, halal product innovation, training, and human resource development, international cooperation, strengthening research and data, promotion and branding, and developing halal infrastructure. Furthermore, in the Industrial Revolution, 4.0, and the new average era, innovation and creativity based on information technology, communication, and digitalization are significant in developing strategies for Islamic economic development. It enables better efficiency, accessibility, and market expansion. The implications of this research provide strategic and innovative recommendations for the Islamic finance industry, government, and economic actors to optimize the implementation of Islamic economics in Indonesia. Furthermore, the novelty of this research article is that it contributes to designing strategies and innovations that the Islamic finance industry, government, and economic actors can implement. These strategies are designed to overcome challenges and take advantage of opportunities to optimize the implementation of Islamic economics in Indonesia.